2012
DOI: 10.1007/s00264-011-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

Dermatan sulphate in methoxy polyethylene glycol-polylactide-co-glycolic acid scaffolds upregulates fibronectin gene expression but has no effect on in vivo osteochondral repair

Abstract: Purpose The purpose of the study was to investigate the effect of dermatan sulphate (DS) addition to biodegradable methoxy polyethylene glycol (MPEG) substituted polylactide-coglycolic acid (PLGA) scaffolds for cartilage repair in vitro and in vivo. Methods Human chondrocytes from eight patients undergoing anterior cruciate ligament reconstruction were isolated and cultured in 5% oxygen on MPEG-PLGA scaffolds ± DS for one, three, seven and 14 days. Analyses were performed using quantitative gene expression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A previous study showed that even trained pathologists in a side-by-side comparison were not able to detect a reduction in cell number by one third. 11 Implementation of semiquantitative scores is often limited by the evaluation of only a few sections through the defect center 42 or at selected locations, 43 indicating that these would represent the morphology of the entire defect. This omission of unbiased sampling may be a potential source of bias despite a comprehensive evaluation of the selected sections.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that even trained pathologists in a side-by-side comparison were not able to detect a reduction in cell number by one third. 11 Implementation of semiquantitative scores is often limited by the evaluation of only a few sections through the defect center 42 or at selected locations, 43 indicating that these would represent the morphology of the entire defect. This omission of unbiased sampling may be a potential source of bias despite a comprehensive evaluation of the selected sections.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the properties of HA and CS, the presence of the other GAGs could contribute to the development of new ECM. Specifically, it has been shown that DS can increase the amount of HA produced by synoviocytes, could reduce the degradation of aggrecan by aggrecanases and triggers the maturation of MSCs (Foldager et al , ). Moreover, aggrecan, which is the main proteoglycan in cartilage, contains KS and, finally, HS exerts a protective effect on cartilage by the downregulation of Mmp3 and Adamts5, proteases which participate in the degradation of aggrecan (Jochman et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A rticular cartilage and subchondral bones may suffer degeneration and functional losses from trauma, osteoarthritis, and other less common diseases, [1][2][3][4][5][6] which may lead to severe pain, joint deformities, and motion losses. Osteochondral defects not only affect the quality of life for individuals but also increase public health spending.…”
Section: The Authors Are From the Department Of Orthopedics (Ml Fh mentioning
confidence: 99%
“…5,7 Moreover, articular cartilage does not have a perfect repairing capability due to a lack of cells and vessels. [2][3][4]8 Surgeons and researchers have been testing different repair and regeneration treatments, such as marrow stimulation technique (microfracture), osteochondral autograft implantation, and autologous chondrocytes transplantation. [9][10][11][12][13] Although these treatments are effective, disadvantages exist, such as the lack of regenerative hyaline cartilage tissue, donor site morbidity, and limited available tissues.…”
Section: The Authors Are From the Department Of Orthopedics (Ml Fh mentioning
confidence: 99%